Maintaining cooperation through vertical communication of trust when removing sanctions - Ann-Christin Posten; Pınar Uğurlar; Sebastian Kube; Joris Lammers (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
An effective way to foster cooperation is to monitor behaviour and sanction freeriding. Yet, previous studies have shown that cooperation quickly declines when sanctioning mechanisms are removed. We test if explicitly expressing trust in players' capability to maintain cooperation after the removal of sanctions, i.e. vertical communication of trust, has the potential to alleviate this drop in compliance. Four incentivized public-goods experiments (N = 2423) find that the vertical communication of trust maintains cooperation upon the removal of centralized (Study 1), thirdparty (Study 2), and peer punishment (Study 3), and this effect extends beyond single interactions (Study 4). In all studies, vertical trust communication increases mutual trust among players, providing support to the idea that vertically communicating trust can be a self-fulfilling prophecy. Extrapolating our findings to natural environments, they suggest that authorities should carefully consider how they communicate the lifting of rules and sanctions.
Keywords: C92; D91; H4; 330; Cooperation; Vertical Trust; Punishment; Public Good; Experiment